Pelatihan Keterampilan Menganyam Tingkat Dasar pada Mahasiswa PIAUD STAI Auliaurrasyidin Tembilahan - Yusnita Yusnita; Rita Kencana; Hasnawati Hasnawati; Muhammadiyah Muhammadiyah; Zulkifli Zulkifli; Zulkarnainsyah Zulkarnainsyah (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The basic level weaving training aims to train skills, making weaving in simple shapes with simple patterns and patterns to motivate and increase creativity in students. the method used in the training is to provide guidance and practical training to PIAUD Semester IV STAI students Auliaurrasyidin Tembilahan. This activity was carried out for 2 days (2 meetings), the first meeting was the process of explaining the material and explaining the tools and materials to be used as well as hands-on practice on how to make basic weaving, namely single, double, double and triple woven. The second meeting of the weaving practitioners used Combination Weaving, Gambir Flowers, and Mata Walik patterns. The training participants were very enthusiastic about the training carried out, and were interested in conducting basic weaving training, more specifically in making a new work from the basic weaving skills that had been taught. Individual trainees can make some of the basic weaves that have been taught, either in single, double, combination and other patterns of weaving.